2020
DOI: 10.1111/cen.14216
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reduces inflammatory metabolic activity of visceral fat assessed by18F‐FDG PET/CT in obese women

Abstract: ObjectivesObesity plays pivotal roles in the increased risk of cardiometabolic disease via induction of the inflammatory reaction from macrophages in visceral adipose tissue (VAT), which may elevate the inflammatory activity of VAT. This prospective study aimed to evaluate whether the inflammatory activity of VAT existed in association with systemic inflammation, and whether exercise could ameliorate the inflammatory activity of VAT assessed by 18F‐fluorodeoxyglucose (FDG) positron emission tomography/computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…The BMI index of T2DM patients in this study group was higher than that of normal subjects, which indicates that T2DM patients had a tendency to be obese. Increased fat tissue is accompanied by inflammatory reactions in obese patients, including the infiltration of macrophages and other immune cells and increased secretion of adipokines, IL‐6, MCP‐1, TNF‐α, and leptin 12 . Inflammatory cytokines interact with the endocrine and immune systems, causing structural changes and dysfunction of pancreatic islet β cells and IR, which ultimately leads to the occurrence of T2DM 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The BMI index of T2DM patients in this study group was higher than that of normal subjects, which indicates that T2DM patients had a tendency to be obese. Increased fat tissue is accompanied by inflammatory reactions in obese patients, including the infiltration of macrophages and other immune cells and increased secretion of adipokines, IL‐6, MCP‐1, TNF‐α, and leptin 12 . Inflammatory cytokines interact with the endocrine and immune systems, causing structural changes and dysfunction of pancreatic islet β cells and IR, which ultimately leads to the occurrence of T2DM 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostics 2021, 11, 164 2 of 10 emission tomography/computed tomography (PET/CT), a non-invasive glucose imaging technique, is well-known to evaluate the inflammatory activity of inflamed tissue, such as vulnerable atherosclerotic plaques [11,12]. As macrophages are also increased in inflamed skeletal muscle [6][7][8], it would also be feasible to use the 18 F-FDG PET/CT to evaluate the inflammatory activity of inflamed skeletal muscle.…”
Section: F-fluorodeoxyglucose (Fdg) Positronmentioning
confidence: 99%
“…For the assessment of skeletal muscle metabolism, psoas muscle (PM) mass has been widely used as a representative index of skeletal muscle mass due to its relative independence from physical activity levels, compared to appendicular muscle mass [13]. Furthermore, recently, Kim et al reported that 18 F-FDG uptake of PM was increased in populations with metabolic syndrome, which is strongly associated with obesity [14]. Thus, we postulated that the metabolic activity of PM, assessed by 18 F-FDG PET/CT, could reflect the inflammatory activity in obesity-induced skeletal muscle inflammation.…”
Section: F-fluorodeoxyglucose (Fdg) Positronmentioning
confidence: 99%
See 2 more Smart Citations